Horses of fire : a novel of Troy - Rhine, A. D. (Dutton, 2023)
"This is the epic retelling of Troy, the most famous war in myth or history, in which four strong yet misunderstood women take center stage, their stories so intricately and beautifully woven together that the result is an utterly spellbinding and immersive historical novel"--